Multimodal Semiotics and Cognitive Schema: A Grounded Theory Analysis of Political Cartoons in Shaping Government Image Perception - Duan, Jingyi; Peng, Jiahe; Tao, Ye (Forum for Linguistic Studies, 2025)
With the shift from “textual narrative” to “visual expression” in the context of new media, cartoons have been increasingly used in political image building and political discourse dissemination due to their multimodal visual characteristics of graphic and textual bi-construction. The public’s perception of the political effect of cartoons is of great significance to the image building of the government. Based on Multimodal Semiotics and Cognitive Schema Theory, this study employs the Grounded Theory approach to explore how multimodal symbols in government-affiliated cartoons activate the cognitive schemas of the audience and subsequently shape their perception of government image. Through in-depth interviews with thirty interviewees from diverse occupational and political backgrounds, the study applied a systematic three-level coding process—open coding, axial coding, and selective coding—until theoretical saturation is achieved. The analysis reveals that: First, multimodal activation mechanism: the cartoonised image of the leader activates the cognitive frame of “friendliness”through exaggerated proportions and soft tones; Second, metaphorical embodiment: the image of the anti-epidemic “Dabai”builds up an all-white protective suit and a smiling expression through the cartoons; Third, cognitive load optimisation: the cartoon of the new health insurance policy replaces the complex text with a flowchart, which reduces the cognitive difficulty of understanding the policy. Based on this, we propose the “Symbol-Cognition Alignment Model”, which reveals the cognitive path of the government cartoons in reconstructing abstract governance concepts through visual-verbal symbol interaction.This model not only deepens the theoretical understanding of the symbol-cognition interaction mechanism in multimodal political communication but also provides practical guidance for government agencies to optimize visual policy communication and enhance the efficiency of public cognition.